Dampak Pembelajaran Daring Pandemi Covid-19 pada Mahasiswa Semester Enam Universitas Muhammadiyah Tangerang - Ishak; Yanah Mulyanah, Euis; Purwasih, Desi (JET (Journal of English Teaching), 2022)
The Covid-19 pandemic has caused changes in various aspects of people’s lives worldwide. Its spread has shifted learning from face-to-face instructions into full online learning from home. The drastic change has motivated researchers to study the phenomenon through various viewpoints. This study aims to find out the impact of online learning during Covid-19 the pandemic on students of EFL learning among the students of Muhammadiyah University, Tangerang. This research used a qualitative approach. The participants were 109 students from four classes of the Sixth Semester at the English Study Program Muhammadiyah University, Tangerang. Data were collected through observation, interview, and documentation. The result of the research showed positive and negative impacts. One of the positive impacts of online learning during Covid-19 was the flexibility of time and places. The negative impact is related to the problem of internet connection.